2004
DOI: 10.1093/jxb/erh119
|View full text |Cite
|
Sign up to set email alerts
|

Altered nitrogen metabolism associated with de-differentiated suspension cultures derived from root cultures of Datura stramonium studied by heteronuclear multiple bond coherence (HMBC) NMR spectroscopy

Abstract: De-differentiation of transformed root cultures of Datura stramonium has previously been shown to cause a loss of tropane alkaloid synthetic capacity. This indicates a marked shift in physiological status, notably in the flux of primary metabolites into tropane alkaloids. Nitrogen metabolism in transformed root cultures of D. stramonium (an alkaloid-producing system) and de-differentiated suspension cultures derived therefrom (a non-producing system) has been compared using Nuclear Magnetic Resonance (NMR) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…S2). This similarity, together with the observation of acetylated polyamines in Arabidopsis and other plants (Mesnard et al, 2000;Fliniaux et al, 2004;Kamada-Nobusada et al, 2008;Hennion et al, 2012), suggested that NATA1 and NATA2 might be polyamine acetyltransferases. Although the predicted catalytic residues of the mammalian enzymes are conserved in the Arabidopsis NATA1 and NATA2 proteins, not all of the known spermine binding residues are present (Supplemental Fig.…”
Section: Arabidopsis Nata1 Functions As a Putrescine Acetyltransferasementioning
confidence: 78%
See 2 more Smart Citations
“…S2). This similarity, together with the observation of acetylated polyamines in Arabidopsis and other plants (Mesnard et al, 2000;Fliniaux et al, 2004;Kamada-Nobusada et al, 2008;Hennion et al, 2012), suggested that NATA1 and NATA2 might be polyamine acetyltransferases. Although the predicted catalytic residues of the mammalian enzymes are conserved in the Arabidopsis NATA1 and NATA2 proteins, not all of the known spermine binding residues are present (Supplemental Fig.…”
Section: Arabidopsis Nata1 Functions As a Putrescine Acetyltransferasementioning
confidence: 78%
“…7B). To date, acetylated polyamines have been reported in only a relatively limited number of plant species (Deagazio et al, 1995;Mesnard et al, 2000;Dufeu et al, 2003;Fliniaux et al, 2004;Kamada-Nobusada et al, 2008;Hennion et al, 2012;Kim et al, 2014). However, this is more likely due to the fact that that these metabolites have not been actively searched for, rather than that they are not present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more, as demonstrated in transformed root cultures of Datura stramonium , cultures with NAA and kinetin caused a de-differentiation of root tissues (Ford et al 1996). In several experiments, the de-differentiation influenced a significant decrease or even the cessation of secondary metabolite production (Fliniaux et al 2004). In our findings, clone H5 line has a rapid accumulation of biomass and secondary metabolite; however, the PGR treatment did not enhance biomass production and tended to reduce fresh weights.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the acetyl-PAs are not the preferred substrates for PAOs in plants [39,55]. Acetylated-Put is directly linked to the pathogen-defense related signals [67] as well as the root cell de-differentiation process, probably as transient metabolite for GABA production [73]. The factors controlling the tri- and tetraamine (Spd and Spm) acetylation remain obscure.…”
Section: Discussionmentioning
confidence: 99%